FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Valencia Jastine, Liana Susanto (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to obtain empirical evidence about the influence of working capital turnover, liquidity, solvency, and firm size toward profitability in manufacturing companies listed in Indonesian Stock Exchange during the period of 2016-2018. This research used 65 samples of manufacturing companies that have been selected using purposive sampling method. Data processing technique in this research using program EViews 10th version. The result of this research indicate that all independent variables used in this research simultaneously have a significant effect on profitability. The result of partially test indicate that solvency has significant effect on profitability, while working capital turnover, liquidity, and firm size have an insignificant effect on profitability.